Education on Responsible and Secure Digital Media Use as a Preventive Measure Against Cyber Risks Among Students of SMA Negeri 1 Baros - Sariyah Sariyah; Chaula Luthfia; Nabilah Falah; Mujadiddah Aslamiyah; Ibnu Pa'qih (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2026)
The rapid development of information technology has brought significant changes to patterns of communication and social interaction, particularly among students who actively engage with digital media. Educational outreach on the wise and secure use of digital media has become increasingly important as an effort to enhance digital legal literacy among students, particularly in improving their understanding of electronic information and transactions, as well as raising awareness of the legal regulations governing activities in digital spaces. This activity aimed to provide students with a comprehensive understanding of the importance of using digital media responsibly and safely, while also preventing legal violations and cyber risks in their online activities. In line with Sustainable Development Goals (SDGs) Number Four on Quality Education, this program seeks to strengthen student’s digital literacy competencies and promote inclusive, equitable, and lifelong learning opportunies in the digital era. The implementation methods included material presentations, interactive discussions, and question-and-answer sessions involving students of SMA Negeri 1 Baros, Serang, Banten. The results of the activity indicated an increase in students’ understanding of the legal aspects of digital media use. Students became more capable of identifying potential legal violations in cyberspace and demonstrated more responsible and cautious behavior in using social media. Furthermore, this activity strengthened the role of schools as educational institutions in fostering law-aware and responsible digital character among students. As a follow-up, sustainable digital literacy programs are required through the integration of law-based digital literacy materials into the curriculum and extracurricular activities, as well as through collaboration among schools, academics, and policymakers to create a digitally competent, critical, and law-abiding younger generation thereby contributing to the achievement of SDGs Number Four through the development of relevant knowledge and skills for responsible participation in the digital society.